2005
DOI: 10.1111/j.1600-0838.2005.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of vasculature and angiogenesis for the pathogenesis of degenerative tendons disease

Abstract: More than 100 years ago Wilhelm Roux (1895) introduced the term "functional adaptation to anatomy and physiology". Compared with other organ systems the functional adaptation processes are best identifiable in the locomotor system, like for example in the two types of tendons: traction and gliding tendons. Traction tendons are tendons where the direction of pull is in line with the direction of the muscle (e.g. Achilles tendon). Gliding tendons (e.g. tibialis posterior tendon) change direction by turning aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
168
0
19

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(191 citation statements)
references
References 70 publications
(110 reference statements)
4
168
0
19
Order By: Relevance
“…the tendon of coracobrachialis muscle). The biomechanical behavior of gliding tendons is fundamentally different from a traction tendon where only tension forces exist; in the contact area between a gliding tendon and the pulley there are strong compressive forces decreasing continuously towards the periphery, while the tensional forces are at their maximum at the outer part of the gliding area and decrease towards the contact area [24] . The overlapping of pressure and tension in the transition zone results in shear stress.…”
Section: Biomechanicsmentioning
confidence: 99%
See 3 more Smart Citations
“…the tendon of coracobrachialis muscle). The biomechanical behavior of gliding tendons is fundamentally different from a traction tendon where only tension forces exist; in the contact area between a gliding tendon and the pulley there are strong compressive forces decreasing continuously towards the periphery, while the tensional forces are at their maximum at the outer part of the gliding area and decrease towards the contact area [24] . The overlapping of pressure and tension in the transition zone results in shear stress.…”
Section: Biomechanicsmentioning
confidence: 99%
“…The overlapping of pressure and tension in the transition zone results in shear stress. The Achilles tendon, under mechanical aspects, is a traction tendon, but its structure doesn't correspond to a traction tendon: gastrocnemius and soleus fibres rotate as they descend to the calcaneal insertion (from anterior to medial the soleus fibres, from posterior to lateral the gastrocnemius ones): such spiralization, the so-called "twisting", confers a mechanical advantage to the tendon but produces an area of concentrated stress where the rotation becomes more marked (approximately 2-7 cm proximal to the insertion onto the calcaneus [17] ; this region is also named Achilles tendon waist [25] : like the waist of a wasp it is reduced in diameter and, as already mentioned, many studies reveal a hypovascularized area in the tendon waist [20] that should be considered an adaptation to the mechanical function and not a sign of degeneration (according to the theory of "causal histogenesis" by Pauwels [24] ). The structure, composition and organization of the matrix of tendons are critically important for their physical properties.…”
Section: Biomechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In approximately 10% of conservatively treated patients, conservative treatment fails and surgery is required [3]. Since tendinopathy appears to be a highly active process of ongoing neovascularization, anti-angiogenic therapies could be a new approach for treating tendinopathies [4]. It has been reported that nerves appear to travel in close association to tendon neovessels [5].…”
Section: Discussionmentioning
confidence: 99%